A Three Component Synthetic Vaccine Containing a β-Mannan T-Cell Peptide Epitope and a β-Glucan Dendritic Cell Ligand - David R. Bundle; Eugenia Paszkiewicz; Hassan R. H. Elsaidi; Satadru Sekhar Mandal; Susmita Sarkar (Molecules, 2018)
Glycoconjugates prepared from the capsular polysaccharide of several pathogenic bacteria and carrier proteins, such as CRM 197 or tetanus toxoid, have been one of the most successful public health measures to be implemented in the last quarter century. A crucial element in the success of conjugate vaccines has been the recruitment of T-cell help and systematic induction of a secondary immune response. The seminal discovery, that degraded polysaccharide fragments with attached peptide are presented to the T-cell receptor of carbohydrate specific T-cells by MHC-II molecules that bind to the peptide component of degraded vaccine, suggests potentially novel designs for conjugate vaccines. A fully synthetic conjugate vaccine was constructed from a 1,2-linked β-mannose trisaccharide conjugated to a T-cell peptide, previously shown to afford protection against Candida albicans. This combined B- and T-cell epitope was synthesized with a C-terminal azidolysine residue for subsequent conjugation by click chemistry. Four copies of a β-1,3 linked hexaglucan dendritic cell epitope were conjugated to an asymmetric dendrimer bearing an alkyne terminated tether. Click chemistry of these two components created a conjugate vaccine that induced antibodies to all three epitopes of the fully synthetic construct.